THE EFFECT OF MATERNAL KNOWLEDGE ON FISH CONSUMPTION IN UNDER-FIVES: A STUDY ON KABILA COMMUNITY HEALTH CENTER, BONE BOLANGO REGENCY - Sunarto Kadir; Moh. Rivai Nakoe (International Journal of Health Science & Medical Research, 2022)
AbstractPoor maternal knowledge of nutrition and health is one of the causes of malnutrition in under-fives. Based on the research problem statement, the present work explores the effect of maternal knowledge on fish consumption in under-fives in the working area of Community Health Center Puskesmas Kabila, Bone Bolango, Regency.This study employed quantitative observation analysis that involved 251 under-fives aged 12 to 59 months selected using a quota sampling method. All univariate and bivariate data were analyzed using a chi-squared test.The result showed that most respondents have a poor understanding of the effect of parental or maternal knowledge on the dietary pattern (232 respondents, 92.4%). Furthermore, fish consumption is considered moderate, as seen in 221 respondents (88.0%). The chi-squared test revealed that the p-value of maternal knowledge is 0.000.In conclusion, maternal knowledge contributes to fish consumption in under-fives. It is expected that the research can provide information for Puskesmas Kabila Bone regarding the condition of people and fish consumption in children living in their working areas.Keywords: Knowledge, dietary pattern, fish, under-fives